Association of sports sampling and training frequency with injury among school-age athletes in Japan. Issue 1 (2nd January 2023) - Nagano, Yasuharu; Oyama, Takashi
ABSTRACT: Background: This study evaluated the status of sports participation and training frequency during school years to identify related factors for injuries in the general Japanese population. Methods: A total of 1, 533 adult participants (762 males, 771 females) retrospectively completed a questionnaire assessing sports participation (single/multisport), training frequency (weekly days of sports participation), and injury history (acute and overuse) at each stage of school (elementary, junior high, and high school). Results: In total, 41.1% of participants reported playing multiple sports in elementary school; this rate decreased to 17.4% in junior high school and 8.9% in high school. Weekly days of sports participation were associated with almost all injuries at each age. Participants who still played multiple sports in junior high school had fewer overuse injuries in junior high school and high school ( P = 0.017; odds ratio (OR) = 0.69; 95% confidence interval (CI) = 0.51–0.94; P = 0.006, OR = 0.66, 95% CI, 0.49–0.89, respectively). The ratio for sports sampling differed between elementary school and older ages. This trend was associated with the prevalence of overuse injuries. Conclusion: Promoting sports sampling through junior high school ages and controlling the training frequency may decrease the occurrence of injuries in young athletes.